Le verre : science et technologie - Barton, James (EDP Sciences, 2005)
This book is a compendium of Mat Hillert's publications. Mat Hillert is a world specialist in metal alloy at the origin of a universal computing code used to calculate the diagrams of phase. This work is in English.
Keywords: Glass.; Glass -- Mechanical properties.; Glass -- Optical properties.; Glass -- Transport properties.; Glass manufacture.; Verre.; Verre -- Propriétés mécaniques.; Verre -- Propriétés optiques.; Verre -- Propriétés de transport.; Verre -- Fabrication.; glass (material); TECHNOLOGY & ENGINEERING -- Chemical & Biochemical.; Glass; Glass manufacture; Glass -- Mechanical properties; Glass -- Optical properties; Glass -- Chemistry of materials; Electronic book.